Pengaruh Pembelajaran Remedial Menggunakan Metode Tutor Sebaya Berbasis Video Animasi terhadap Motivasi Belajar pada Materi Kardiovaskular - Setiyani, Riska; Narsan, Vifty Octanarlia (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
This research was conducted to look at remedial learning using the peer tutoring method based on animated videos on students' learning motivation on cardiovascular material. The sampling technique uses purposive sampling technique. The research method used is a descriptive quantitative method. The population and sample in the research were 28 students in class XI MIA 4 MANegeri 1 East Lampung with a sample of 24 students who experienced remedial treatment. The research instrument used was a learning motivation questionnaire sheet which refers to 6 indicators of learning motivation: 1) the desire and desire to learn; 2) there is encouragement and need to learn; 3) there are hopes and aspirations for the future; 4) there is appreciation for learning; 5) there are interesting activities in learning; and 6) there is a conducive learning situation, so that students can learn well. Based on the research results, it was found that there was an influence in the use of animated video-based peer tutoring methods on student learning motivation in remedial learning on cardiovascular system material.